Penggunaan Media Flash Card Untuk Meningkatkan Keterampilan Berbicara Bahasa Inggris Pada Siswa Kelas V Mi Al-Husna Meruya Utara Jakarta Barat Tahun Ajaran 2022/2023 - Devi, Sevtia; Rosnaningsih, Asih; Nurfadhillah, Septy (Peneliti.net, 2024)
This study aims to improve students' English speaking skills by using flash card media in English subjects. This research was carried out at MI Al-Husna Meruya Utara, West Jakarta, class V in the even semester of the 2022/2023 academic year. This type of research is Classroom Action Research (CAR) model Kemmis & Mc. Taggard with the subject of this research are 30 students. This study was designed in three cycles, each cycle consisting of two meetings, each meeting consisting of four stages, namely planning, implementing, observing, and reflecting. The results showed that there was an increase in student learning outcomes through flash card media for Class V MI Al-Husna students. This was proven by the results of data analysis. with an average score of 68, then in cycle I the learning outcomes of students who achieved KKM increased by 63% with an average score of 71.52, in cycle II the KKM reached 83% with an average score of 79.8, and in Cycle III achieved KKM 97% with an average score of 86.4. Thus it can be concluded that using Flash Card Media can improve English speaking skills in fifth grade students at MI Al-Husna Meruya Utara, West Jakarta.